INTENTION TO PURCHASE THE PRIVATE LABEL BRAND: THE ROLES OF FINANCIAL RISK PERCEPTION, PRICE, AND VALUE CONSCIOUSNESS FOR CONSUMERS OF HYPERMARKET IN SURABAYA - Veronika Rahmawati (Universitas Hayam Wuruk Perbanas, 2013)
The consumers’ perception towards private label is considered important and therefore, it shouldbe understood by the retailers. This is true when related to the price and quality of private labels.In addition, these factors are the main consideration when the consumers purchase the privatelabel. This research focuses on investigating the effect of financial risk perception on value consciousnesswith price perception as moderating variable which is moderated also by purchaseintention to private label. The criteria for the sample consist of such as women of 25 years oldwho shopped and bought private label in hypermarkets. This covers 150 respondents selectednon-randomly. The results show that financial risk perception and value consciousness influencepurchase intention. But, the price perception is not the moderating variable between financialrisk perception and value consciousness. Thus, it can be concluded that price perception is notthe moderating between financial risk perception and value consciousness toward purchase intentionfor private label brand for the consumers in hypermarkets in Surabaya.